Ready for Prime Time? Using Normalization Process Theory to Evaluate Implementation Success of Personal Health Records Designed for Decision Making - Davis, Selena (Frontiers in Digital Health, 2020)
Personal health records designed for shared decision making have the potential to engage patients and provide opportunities for positive health outcomes. Given the limited number of published interventions that become normal practice, this pre-implementation evaluation of an integrated shared decision making-personal health record system (e-PHR) was underpinned by Normalization Process Theory (NPT). The theory provides a framework to analyze cognitive and behavioral mechanisms known to influence implementation success; these include coherence, cognitive participation, collective action, and reflexive monitoring. A mixed methods investigation was utilized to explain the work required to implement e-PHR and its potential to integrate into practice. Patients, care providers and EHR/clinical leaders (n=27) offered a rich explanation of the implementation work. Reliability tests of the NPT-based instrument negated the use of scores for coherence (α = 0.33) and reflexive monitoring (α = 0.55) mechanisms. Participants indicated that e-PHR made sense ('coherence') as explained by two qualitative themes: game changing technology and sensibility of change. Participants appraised e-PHR ('reflexive monitoring') as explained by two themes: reflecting on value and monitoring and adapting. The combined qualitative and quantitative results for the other two NPT mechanisms corroborated. Participants strongly agreed (score=4.6/5) with 'cognitive participation' processes requiring an investment in commitment, explained by two themes: sharing ownership of the work and enabling involvement. Weak agreement (score=3.6/5) was observed with 'collective action' processes requiring an investment in effort, explained by one theme: uncovering the challenge of building collective action, and three sub-themes: assessing fit, adapting to change together, and investing in the change. Finally, participants strongly agreed (score=4.5/5) that e-PHR would positively affect engagement in self-management decision-making in two themes: care is efficient, and care is patient-centered. Overall, successful integration of e-PHR will only be attained when systemic effort is invested to enact it. Additional investigation is needed to explore the collective action gaps to inform priorities and approaches for future implementation success. This research has implications for patients, care providers, EHR vendors, and the healthcare system for improving the effectiveness and efficiency of patient-centric services. Findings confirm the usefulness of NPT for planning and understanding implementation success of PHRs.